2021
DOI: 10.3390/sym13091699
|View full text |Cite
|
Sign up to set email alerts
|

Dispersionless BKP Equation, the Manakov–Santini System and Einstein–Weyl Structures

Abstract: We construct a map from solutions of the dispersionless BKP (dBKP) equation to solutions of the Manakov–Santini (MS) system. This map defines an Einstein–Weyl structure corresponding to the dBKP equation through the general Lorentzian Einstein–Weyl structure corresponding to the MS system. We give a spectral characterisation of reduction in the MS system, which singles out the image of the dBKP equation solution, and also consider more general reductions of this class. We define the BMS system and extend the m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Another very interesting and geometrically motivated trend is presented by the article by L.V. Bogdanov [3], devoted to studying a map from solutions of the dispersionless BKP (dBKP) equation to solutions of the Manakov-Santini (MS) system. It is shown that this map defines an Einstein-Weyl structure corresponding to the dBKP equation through the general Lorentzian Einstein-Weyl structure, corresponding to the MS system.…”
mentioning
confidence: 99%
“…Another very interesting and geometrically motivated trend is presented by the article by L.V. Bogdanov [3], devoted to studying a map from solutions of the dispersionless BKP (dBKP) equation to solutions of the Manakov-Santini (MS) system. It is shown that this map defines an Einstein-Weyl structure corresponding to the dBKP equation through the general Lorentzian Einstein-Weyl structure, corresponding to the MS system.…”
mentioning
confidence: 99%